2012
DOI: 10.1292/jvms.11-0214
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography and Radiographic Lymphography of the Thoracic Duct by Subcutaneous or Submucosal Injection

Abstract: ABSTRACT. A simple method of lymphography of the thoracic duct was investigated. Using three female beagles, contrast media were administered rectally, vaginally and into the perianal tissue. The administration sites were gently massaged, and imaging was carried out at constant intervals using computed tomography and radiograph. Moreover, Indian ink was administered into the rectum mucous membrane in dogs for proof of this method of lymphography, and the lymph drainage routes were observed. The investigation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…Methylene blue has been used as a contrast agent for both open and minimally invasive intraoperative techniques . A number of sites for contrast injection have been described, including the popliteal lymph node, jejunal lymph node, mesenteric lymphatic branches, subcutaneous or submucosal tissues, web of the digits, and diaphragm …”
Section: Discussionmentioning
confidence: 99%
“…Methylene blue has been used as a contrast agent for both open and minimally invasive intraoperative techniques . A number of sites for contrast injection have been described, including the popliteal lymph node, jejunal lymph node, mesenteric lymphatic branches, subcutaneous or submucosal tissues, web of the digits, and diaphragm …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that subcutaneously administered WIC is rapidly absorbed into the local lymphatic channels. [8, 9, 11, 12, 28, 30, 31] However, such studies only describe evaluating SLN and lymphatic channels using computed tomography. Development of a more economic and readily available technique for SLN mapping could be beneficial to veterinary oncology patients.…”
Section: Introductionmentioning
confidence: 99%
“…2). CT scan lymphangiography was performed by injection of contrast media in perianal subcutaneous tissue, as previously described in dogs by Ando et al (2012). The perianal area was clipped and surgically prepared.…”
Section: Introductionmentioning
confidence: 99%
“…Laparotomy or more recently laparoscopy may be needed to perform the mesenteric injection (Brisson et al, 2006). In this case report, an approach described by Ando et al (2012) was applied. Ando et al (2012) reported an appropriate visualization of the thoracic duct 5 minutes after contrast media injection in a healthy Beagle dog.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation